Computer information systems and industrial management : 17th International Conference, CISIM 2018, Olomouc, Czech Republic, September 27-29, 2018, Proceedings /: 17th International Conference, CISIM 2018, Olomouc, Czech Republic, September 27-29, 2018, Proceedings. (2018) - Unknown
No abstract available